Study on coal facies evolution and the coal-forming environment of the L2 coal seam in Juhugeng mine, Muli coalfield, Qinghai province - Li, Jing; Wang, Lu (Frontiers in Earth Science, 2025)
Maceral composition in coal varies significantly under the influence of different sedimentary environments. This study applies coal petrology techniques to elucidate the controlling mechanisms of coal-forming environments on macerals, focusing on the L2 coal seam from the Juhugeng mine in the Muli coalfield. The results reveal that the lower section of the L2 coal seam is predominantly composed of semi-bright coal, transitioning upward into durain and semi-dull coal. Vitrinite is the dominant maceral, followed by inertinite, while clay minerals constitute the primary inorganic component. Based on vertical variations in coal facies, the L2 coal seam is subdivided into three evolutionary stages from bottom to top: a wet forest swamp facies, a wet herbaceous swamp facies, and a return to wet forest swamp facies. These transitions reflect dynamic changes in peat-forming conditions, likely driven by subtle shifts in hydrology, vegetation input, and clastic influx.